2011
DOI: 10.1111/j.1749-7345.2011.00455.x
|View full text |Cite
|
Sign up to set email alerts
|

Partial Replacement of Fish Meal by Fermented Soybean Meal in Diets for Black Sea Bream, Acanthopagrus schlegelii, Juveniles

Abstract: The effect of fish meal (FM) substitution with fermented soybean meal (FSBM) in the diets of the carnivorous marine fish, black sea bream, Acanthopagrus schlegelii, was investigated. An 8-wk feeding trial was conducted with black sea bream (11.82 ± 0.32 g; mean initial weight) in indoor flowthrough fiberglass tanks (25 fish per tank). Six isonitrogenous and isoenergetic diets were formulated, in which FM was replaced by FSBM at 0% (control diet), 10% (FSBM10), 20% (FSBM20), 30% (FSBM30), 40% (FSBM40), or 50% (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
92
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(124 citation statements)
references
References 78 publications
15
92
2
1
Order By: Relevance
“…More studies to elucidate the reason why abalone fed the diet containing fermented soybean meal showed poorer growth performance than that fed diet containing soybean meal is needed. Unlike this study, however, d ietary inclusion of the fermented plant protein sources, such as soybean meal and cottonseed meal produced promising effect on performance of fish (Lim & Lee, 2011;Zhou et al, 2011).…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…More studies to elucidate the reason why abalone fed the diet containing fermented soybean meal showed poorer growth performance than that fed diet containing soybean meal is needed. Unlike this study, however, d ietary inclusion of the fermented plant protein sources, such as soybean meal and cottonseed meal produced promising effect on performance of fish (Lim & Lee, 2011;Zhou et al, 2011).…”
Section: Discussionmentioning
confidence: 47%
“…Dietary inclusion of fermented plant protein sources, such as soybean and cottonseed meals also produced a promising effect on performance of Nile t ilap ia, Oreochromis niloticus Linne and black sea bream, Acanthopagrus schlegeli Bleeker (Lim & Lee, 2011;Zhou et al, 2011). A study by Kim et al (2015) on abalone, H. discus Reeve revealed that 1000 g/kg substitution of L. japonica with rice bran, [an agricu lture byproduct and rich in the nutrients such as crude protein and vitamins (Gao, Kaneko, Hirata, Toorisaka, & Hano, 2008)], at 200 g/kg in the diet was successful in terms of abalone weight gain.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the improved growth may be attributed mostly to the improvement in the nutritional value and the elimination of antinutritional factors in fermented soybeans [3]. Fan et al [26] found that markedly lower concentrations of antinutritional components such as phytic acid, lectin, and urease were found in FSBM as compared with nonfermented SBM. Similarly, Wu and Jing [7] suggested that fermentation could improve protein digestibility, essential amino acid index (EAAI) and protein efficiency ratio (PER) of soybean meal (SBM).…”
Section: Treatmentsmentioning
confidence: 99%
“…Several studies have reported that even when heat-treated, standard (solvent-extracted) and full-fat SBM-containing feeds supplemented with limiting amino acids, can lead to decreased growth and energy digestibility in farmed species (Merrifield and Olsen 2011;Krogdahl et al 2003). However, considerable success in partially or totally replacing FM with SBM in diets for fish species has been achieved (El-Saidy and Gaber 2002; Yaghoubi et al 2016;Zhou et al 2011).…”
Section: Introductionmentioning
confidence: 99%